The Influence of Caregiver, Social Support and Quality of Life in Elderly People with Type 2 Diabetes Mellitus in Thailand (International Journal of Nursing Education, 2026)
Background: Diabetes mellitus significantly impacts the quality of life (QoL) of older adults, particularly in rural Thailand.Beyond clinical management, caregiver support and social networks are considered to be crucial determinants ofwell-being. However, research regarding these factors remains limited in this specific context. This study examines theinfluence of caregiver, perceived social support, and QoL among elderly with type 2 diabetes mellitus.Methods: A cross-sectional study was conducted among 366 elderly patients with type 2 diabetes mellitus(aged ≥60years). Data were collected by structured questionnaires. Multiple linear regression analyses were performed to examineassociations while controlling sociodemographic and health-related variables.Results: The mean age of participants was 67.70 years (SD = 4.99), with 69.67% female. Most received care from a spouse(54.37%) or family members (28.69%), while 16.94% had no caregiver. High perceived social support(β = 0.507, p
Keywords: Caregiver, Social Support, Quality of Life, Elderly, Diabetes Mellitus Thailand.